2005
DOI: 10.1177/153303460500400614
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Tyrosine Kinase Inhibitors in Modifying the Response of Tumor Microvasculature to Radiotherapy

Abstract: The response of the tumor microvasculature to ionizing radiation can be modified to improve tumor control in preclinical mouse models of cancer. Recent studies have shown that a variety of cancer drugs can improve the response of cancers to radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…HPIs have been shown to attenuate angiogenesis in numerous tumor models. Previous reports have shown that attenuating the PI3K/Akt pathway enhances the antiangiogenic effect of ionizing radiation (15,22,30,36,37). In the current study, we examined the effect of HPIs and radiation on endothelial cell function.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…HPIs have been shown to attenuate angiogenesis in numerous tumor models. Previous reports have shown that attenuating the PI3K/Akt pathway enhances the antiangiogenic effect of ionizing radiation (15,22,30,36,37). In the current study, we examined the effect of HPIs and radiation on endothelial cell function.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, a recent report suggests that HPIs have the ability to sensitize tumor cells with constitutively active PI3K signaling to the cytotoxic effects of ionizing radiation (12). We and others have previously shown that the PI3K/Akt pathway is activated in HUVECs after ionizing radiation (18,22,30,32,33) and compounds that inhibit this pathway sensitize endothelial cells to radiation. In the current study, nelfinavir was found to attenuate the phosphorylation of Akt as well as Erk to a lesser extent after 3 Gy, a clinically relevant dose.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We and others have shown that radiation induces Akt phosphorylation (4,29,(34)(35)(36). A, endothelial cell closure assay is shown in which 80% confluent HUVEC were subjected to a gap formation using a 200 AL pipette tip.…”
Section: Discussionmentioning
confidence: 99%
“…Many proangiogenic growth factors regulate angiogenesis through PI3K/Akt and MKK/ ERK signaling pathways (Kim et al, 2004;Lu et al, 2005;Perona, 2006). MKK/ERK signaling pathway has been shown to play a crucial role in tumori- genesis and tumor metastasis (Ward et al, 2001;Huang et al, 2008), and sustained activation of ERK has been established as a requirement for angiogenesis (Berra et al, 2000;Dong et al, 2001;Depeille et al, 2007).…”
Section: Introductionmentioning
confidence: 99%